2011
DOI: 10.1111/j.1582-4934.2010.01166.x
|View full text |Cite|
|
Sign up to set email alerts
|

Hsp72 mediates TAp73α anti-apoptotic effects in small cell lung carcinoma cells

Abstract: The transcription factor p73, a member of the p53 family of proteins, is involved in the regulation of cell cycle progression and apoptosis. Due to alternative promoters and carboxy-terminal splicing, the P73 gene gives rise to a range of different isoforms. Interestingly, a particular increase in expression of the TAp73α isoform has been reported in various tumours. In addition, TAp73α has been shown to inhibit Bax activation and mitochondrial dysfunctions and thereby to confer small cell lung carcinoma (SCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 46 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…Previously, we have shown that TAp73alpha can repress drug-induced apoptosis in a cell-type specific manner. We demonstrated this effect to be exerted upstream of the mitochondria, at the level of Bax activation [22, 44]. Here, we provide an additional mechanism in support of the anti-apoptotic effect of TAp73alpha.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Previously, we have shown that TAp73alpha can repress drug-induced apoptosis in a cell-type specific manner. We demonstrated this effect to be exerted upstream of the mitochondria, at the level of Bax activation [22, 44]. Here, we provide an additional mechanism in support of the anti-apoptotic effect of TAp73alpha.…”
Section: Discussionsupporting
confidence: 55%
“…We have shown that TAp73alpha is able to prevent VP16-induced loss of mitochondrial membrane potential in SCLC cells [22, 44]. To explore whether the protective effect of TAp73alpha over-expression on caspase-2 induced apoptosis involve repression of mitochondrial dysfunction, the mitochondrial transmembrane potential was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nyman et al . , an error occurred in Figure 1 Panel B. The G3PDH immunoblot presented for HEK293 cells is a duplication of the G3PDH immunoblot related to H82 cells.…”
mentioning
confidence: 99%